Strong two-scale convergence and corrector result for a receptor-based model of intercellular communication - Marciniak-Czochra, Anna (IMA journal of applied mathematics, 2012)
A rigorous derivation of the macroscopic reaction-diffusion models describing the interplay between the nonhomogeneous receptors-ligand binding on cell surfaces and the signalling molecules diffusing in the intercellular space has been carried out by Marciniak-Czochra and Ptashnyk [(2008) SIAM J. Mat. Anal., 40, 215-237] using the method of homogenization. In the present paper, we extend the result to strong two-scale convergence of the model variables using the convergence of the respective energies and establish a corrector result.